Assessement of Candida utilis growth by voltammetric reduction of acids using microelectrodes - Rodrigues, Astride (2004)
A voltammetric method for the evaluation of the microbial growth using platinum microelectrodes is proposed. This new method is based on the electrochemical reduction of acids produced by the yeast Candida utilis in liquid medium containing glucose as carbon and energy source and ammonium ions as nitrogen source. Current intensities, from linear sweep and square wave voltammetry, were compared with the corresponding values of absorbance at 640 nm (A640nm) resulting from the light scattering of cell suspensions. The equivalence between turbidimetry and electrochemical measurements was checked in experiments performed in growing cultures and in cell suspensions prepared from the dilution of cell cultures. The growth curves defined by either current intensities (IP or IL) or A640nm measurements were similar and displayed characteristic growth phases in a closed system. Exponential growth rates estimated both from turbidimetry and voltammetric techniques were the same.